Nowhere to run eaudiobook - Box, C. J. (Joe Pickett, 2010)
Edgar, Anthony, Macavity, Gumshoe, and Barry Award winner C. J. Box crafts the 10th explosive entryfrom his acclaimed Joe Pickett series. When bizarre incidents start piling up, including the disappearance of afemale runner, Joe heads into the mountains near Baggs, Wyoming, to investigate. It doesn't take long before therugged game warden wishes he hadn't bothered. ". an intense story . Highly recommendedLibrary Journal